FEATURES OF THE ATTITUDE TO THE PHILOSOPHY OF COMPROMISE IN THE TEACHINGS OF NAQSHBANDI (Scientific journal of the Fergana State University, 2023)
This article describes the essence of the concept of compromise, its philosophical analysis and its unique aspects in the teaching of Naqshbandiya, the views on the characteristics of the manifestation of the attitude to compromise in ensuring social stability in the activities of the great representative of this doctrine, Khoja Ahror Vali.